2017
DOI: 10.1016/j.nut.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparing nutritional requirements, provision and intakes among patients prescribed therapeutic diets in hospital: An observational study

Abstract: Hospitalized patients prescribed therapeutic diets (particularly fluid-only diets) are at risk for malnutrition. Further research is required to determine the most effective strategies to improve nutritional provision and intake among patients prescribed therapeutic diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 33 publications
4
47
0
3
Order By: Relevance
“…Lastly, the palatability, meal size/options, nutritional content, and/or repetitive nature of dietary items offered on the liquid and solid diets were raised as factors contributing to poor oral intakes among patients. Indeed, this is consistent with previous studies investigating nutrition provision and intakes among patients prescribed liquid diets, 11,25 and previous work undertaken at the study site exploring postsurgical patients' food preferences and perceptions. 44 Collectively, these results indicate that hospitals need to ensure postsurgical patients have access to a variety of appropriate, adequate, and timely foods and that patients and staff are aware of the dietary options available to them.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lastly, the palatability, meal size/options, nutritional content, and/or repetitive nature of dietary items offered on the liquid and solid diets were raised as factors contributing to poor oral intakes among patients. Indeed, this is consistent with previous studies investigating nutrition provision and intakes among patients prescribed liquid diets, 11,25 and previous work undertaken at the study site exploring postsurgical patients' food preferences and perceptions. 44 Collectively, these results indicate that hospitals need to ensure postsurgical patients have access to a variety of appropriate, adequate, and timely foods and that patients and staff are aware of the dietary options available to them.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the majority of staff expressed positive attitudes toward the role of nutrition in healing and recovery after surgery. However, staff recognized that patients were often commenced on solid diets several days after surgery and ate poorly while in hospital, findings consistent with observational studies of feeding practices among postoperative gastrointestinal patients . Many staff attributed variability in the prescription of solids to differences in surgeons’ preferences and patient‐related factors, such as the incidence or risk of postoperative ileus.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In a recent systematic review of current postoperative feeding practices it was identified that only 40% of included studies reported time to first liquid or solid feed, and only 22% reported time to first solid feed that were consistent with current EBG recommendations . Further, when solids were commenced, restricted diets, which are often nutritionally inadequate and have little scientific purpose in the context of postoperative nutrition care, were commonly used prior to the commencement of a regular diet . Collectively, these findings suggest a gap between recommendations and practice for initiating and progressing patients onto nutritionally adequate diets following surgery.…”
Section: Introductionmentioning
confidence: 98%
“…Ideally, meal times would have been observed; however, this was not practical within the time constraints of this audit; reliability and validity of overall intakes and the proportion of patients meeting both the Digest standards and individual requirements are therefore reduced. This could be improved using repeat 24‐h recalls , although weighed food intakes would provide the most accurate results for patients meeting their nutritional requirements .…”
Section: Discussionmentioning
confidence: 99%